Pengaruh Ukuran Perusahaan, Laba/Rugi Operasi, Opini Auditor Dan Reputasi Auditor Terhadap Audit Delay(Studi Empiris pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia tahun 2010- 2014) - Putri, Yeni Oktavia Melati; , Suyatmin Waskito Adi, SE,M.SI (2016)
This study aims to provide empirical evidence of influence: the size of the company, profit / loss surgery, the auditor's opinion and reputation of auditors to audit delay in Manufacturing companies listed in Indonesia Stock Exchange 2010-2014. This research was conducted using secondary data. The sample in this study were 24 companies listed on the Indonesian Stock Exchange (BEI) during the year 2010-2014. The analytical method used is multiple linear regression analysis. The results of this study prove that the variable firm size affect the audit delay, while profit / loss surgery, the auditor's opinion, and does not affect the auditor's reputation audit delay in manufacturing companies in the Indonesia Stock Exchange. Keywords: audit delay, the size of the company, profit / loss surgery, the auditor's opinion, and the auditor's reputation.